2010
DOI: 10.1002/cjce.20274
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient high solids loading agitation for the mineral industry

Abstract: This paper presents results of a study on minimising the specific power for off-bottom solids suspension in mixing tanks at a high solids concentration. It was found that major savings in the specific power required to suspend solids at high concentrations can be achieved by removal of baffles. This is particularly relevant to applications where chemical reaction rate is not affected by the mixing rate, such as that often occurs in the mineral industry. The specific power at the just off-bottom solids suspensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…It can be seen that the normalized solids‐bed height ( H B / H ) is zero at N js , and increases with a decrease in impeller speed. This method of using settled solids‐bed height for determining N js has been demonstrated by Wu et al2, 8, 9, 21 to be quite reliable for suspensions with high‐solids concentrations.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…It can be seen that the normalized solids‐bed height ( H B / H ) is zero at N js , and increases with a decrease in impeller speed. This method of using settled solids‐bed height for determining N js has been demonstrated by Wu et al2, 8, 9, 21 to be quite reliable for suspensions with high‐solids concentrations.…”
Section: Methodsmentioning
confidence: 89%
“…In this work, therefore, a method recommended by Wu et al2, 8–9 was used to determine N js . In this method, the bed height of the settled solids at the tank bottom was used as a means of determining N js .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kasat et al (2005) concluded that the choice of a proper impeller for solid suspension is the key in achieving economic success in the process. Wu et al (2010a) found that the removal of baffles can play an effective role in drastically reducing the power draw for suspending the particles off the tank bottom. They found that about a 70% energy saving can be achieved under high solids loading (>0.40) under unbaffled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Estas son descritas en tres categorías típicas: las de orden de magnitud del diámetro (o tamaño) de la máquina, fluctuaciones periódicas asociadas al paso de álabe y perturbaciones de pequeña escala, asociadas con las estructuras turbulentas del flujo. Para el diseño de tanques agitadores, se han establecido técnicas experimentales con el propósito de conocer parámetros de funcionamiento, el consumo de potencia, homogeneidad de fluidos, entre otros (Zwietering, 1958;Wu et al, 2006;Wu et al, 2010a;Wu et al, 2010b;Ibrahim, 2012). Además, a partir de ensayos experimentales se logra obtener correlaciones empíricas mediante la relación entre variables y parámetros de funcionamiento.…”
Section: Introductionunclassified